Pembentukan Karakter Peserta Didik melalui Penguatan Kompetensi PPKn: Studi Kasus di SMAS GKPI Padang Bulan - Napitupulu, Kristin Hawini; Setiawan, Deny (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
This research aims to determine whether strengthening PPKn competencies can shape the character of students at SMAS GKPI Padang Bulan Medan. The character theory used as a reference is according to expert Thomas Licona who divides character education into 3 aspects, namely; knowledge (Moral Knowledge), emotions (Moral Feeling), and actions (Moral Action). This research uses quantitative descriptive methods. The research implementation time is approximately one month, namely April 17 to May 18 2024. Data collection techniques were carried out using observation, interviews and documentation. The data collection instruments used in this research were Likert Scale questionnaires and open questionnaires. The research subjects were determined based on samples selected using purposive sampling techniques, namely class X-3 students and 3 PPKn teachers. The type of data in this research uses primary and secondary data. The data analysis technique used is simple descriptive statistics, namely table analysis and percentages P= F/N x 100%, with categories 0-69% (Low), 70-89% (Medium), 90-100% (High) calculated based on the provisions of the Likert Scale score. The research results show that the character of the students there is categorized as